Exploration of influence of led spotlights on quality of electric energy - V. P. Kuzmenko; S. V. Solyony (Омский научный вестник)
The results of the study and assessment of the quality of electrical energy measured at a separate phase in the existing electrical installation of the building, with a load in the form of LED floodlights are presented. The problem of the negative impact on the quality of electrical energy of switching power supplies of electronic devices, typical for this type of electrical load, is considered.